PENGARUH PENERAPAN METODE PEMBELAJARAN RESOURCE BASED-LEARNING (RBL) DENGAN MEMANFAATKAN INTERNET TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMA N 4 PADANG TAHUN PELAJARAN 2008/2009 - Ardi Ardi; Anizam Zein; Rica Rusticawaty (Ta'dib, 2010)
This study was conducted to figure out the influence of Resource-based Learning (RBL) learning method using internet toward learning achievement in Biology subject. This study employed Post-test only Control Group Design. The population was the first semester of the tenth grade students of SMAN 4 Padang in 2008/2009 academic year. They were distributed into 8 parallel classes. The sample was taken by employing purposive sampling technique. After deciding two classes to become the sample by using coin flipping technique, class X.6 and X.5 were chosen as the experimental and control groups respectively. Data were analyzed by using t-test. Based on the data analysis, it was found that the value of t-calculated was 3.87 under the degree of freedom 95% (α=0.05) and the value of t-table was 2.00 under the degree of freedom of 69. Therefore, t-calculated was higher that t-table. This means that the alternate hypothesis was accepted. It can be concluded that Resource-based Learning (RBL) learning method using internet gives significant influence toward learning achievement in Biology subject of the tenth grade students of SMAN 4 Padang in 2008/2009 academic year.Kata kunci: metode pembelajaran, resource based learning, internet, hasil belajar, biologi